Determinants of purchase behaviour among family takaful participants - Nur Syafiqah Razmi; Nur Syahirah Shaharudin; Nur Syahirah Yusri; Nur Syamim Arifah Mat Zali (2023)
Takaful is defined as “a scheme based on brotherhood, solidarity and mutual assistance which provides for mutual financial aid and assistance to the participants in case of need whereby the participants mutually agree to contribute for that purpose” (Amir, 2020). The types of misfortune can be fire, flood, and other natural disasters. Simply put, insurance act as monetary assistance through a simple agreement between two parties which is insurer and insured. Conventional insurance agreement not allowed in Islam due to inclusion of prohibitive elements such as riba, gharar and maysir (Ahmed Salman, 2019). Takaful is founded on the idea of reciprocal solidarity and indemnity that safeguards participants who encounter certain risks and dangers (Alif Fianto, 2014). The takaful system must adhere to Islamic ethics and standards in order for Muslims to embrace it, which necessitates the existence of values like collaboration (Ta'wun) and giving (Tabarru') necessary (Salleh & Afthanorhan, 2018).